Cold-Renneted Milk Powders for Cheese Production: Impact of Casein/Whey Protein Ratio and Heat on the Gelling Behavior of Reconstituted Rennet Gels and on the Survival Rate of Integrated Lactic Acid Bacteria - Malou Warncke; Sonja Keienburg; Ulrich Kulozik (Foods, 2021)
The idea was to develop powders for fresh/hard cheese or quark production comprising milk proteins in optimal composition and functional properties for manufacturing each of those cheese types. The aim was to avoid whey protein drainage by their prior removal or by their heat-induced structural integration in the curd. The pre-renneted powders already contain additives such as starter cultures and calcium chloride to instantaneously form homogeneous curds upon reconstitution. The impact of the casein/whey protein ratio (86:14 by ultrafiltration and 98:2 by microfiltration) and upfront heat treatment (80 °C/30 min) on the gelling behavior of reconstituted rennet gels and on the survival rate of integrated Lactobacillus paracasei ssp. paracasei F19 was investigated. The assessment criteria for the rennet gelation were curd firming rate, gel strength, and whey drainage. Furthermore, the amount of integrated whey proteins and the resulting cheese yield were evaluated. It could be shown that heating had a positive effect on the viable cell count of the bacteria after spray drying and on the gelation behavior of the reconstituted ultrafiltration concentrates. The curd firming rate and the gel strength could be increased to higher values than the reconstituted microfiltration concentrate at 25% total solids.